Tourist perception during the COVID-19 Pandemic on the Hotel sector of Aracaju / SE using the Electronic Data Scraping (EDS) method (Research, Society and Development, 2020)
This research is based on the understanding of opinion data collected at Online Travel Agencies regarding the perception of users staying in the city of Aracaju, capital of the State of Sergipe, through a mixed approach of exploratory analysis, with a quantitative approach.  Thus, the Electronic Data Scraping (EDS) method was performed, with further study of the users' discourse using the lexical analysis method of the contents using the IRaMuTeQ software. The highest scores for accommodation providers were between 8 and 10, in a score ranging from 1 to 10, demonstrating a good general acceptance of the services offered.  Among the positive points most declared by users is the low cost, politeness of service, security and travel.  The most observed negative points and difficulties were physical structure and thermal comfort. The results obtained by this method can be easily used by companies in the city of Aracaju for commercial prospecting within domestic tourism, as well as by public agencies that wish to attract more visitors to the capital of Sergipe.